PERNYATAAN STANDAR AKUNTANSI KEUANGAN (PSAK) 16 DAN REVALUASI ASET TETAP PADA RUMAH SAKIT UMUM DAERAH GUNUNGSITOLI KABUPATEN NIAS PROVINSI SUMATERA UTARA - Takiyuddin Takiyuddin (Universitas Islam Islam Sumatera Utara, 2018)
The revaluation of fixed assets is regulated in PSAK No. 16 (PSAK 16) issued by The Indonesian Institute of Accounting. The fixed asset is one of the balance sheet items that should be managed as well as possible. The main purpose of this research is to analyze the accounting system of fixed assets of Gunungsitoli General Hospital of Nias Regency, North Sumatra with reference to Statement of Financial Accounting Standards number 16 (PSAK 16) issued by the Indonesian Institute of Accountants (IAI). This study used a qualitative approach with instrument data collection through documents and interviews. Based on the analysis on the data and information obtained, the results show that the revaluation of the fixed asset accounting policy applied by the hospital is appropriate but limited to 8 items of equipment of 283 items. This means many items are not included to be revalued so that they are not in accordance with Statement of Financial Accounting Standards Number 16 (PSAK 16).